Perspectives on Arabic linguistics XXXI papers from the Annual Symposium on Arabic Linguistics, Norman, Oklahoma, 2017 - Khalfaoui, Amel; Haddad, Youssef A., 1972- (Studies in Arabic linguistics ;, 2019)
This volume brings together ten peer-reviewed articles on Arabic linguistics. The articles are distributed over three parts: phonetics and phonology, sociolinguistics and pragmatics, and language acquisition. Including data from North African, Levantine, and Gulf varieties of Arabic, as well as Arabic varieties spoken in diaspora, these articles address issues that range from phonetic neutralization and diminutive formation to diglossia, dialect contact, and language acquisition in heritage speakers. The book is valuable reading for linguists in general and for those working on descriptive and theoretical aspects of Arabic linguistics in particular.